The Effect of Brimonidine 0.1% on Disc Hemorrhage in Primary Open-Angle Glaucoma Patients - Nitta K (Dove Medical Press, 2020)
Koji Nitta,1,2 Shiro Shimamoto,3 Ryotaro Wajima,2 Gaku Tachibana,2 Yutaro Yamada,1,2 Miyuki Domoto,1 Ryuji Takeda,4,5 Yoshinari Takahashi,6 Kazuhisa Sugiyama2 1Fukui-ken Saiseikai Hospital, Fukui, Japan; 2Department of Ophthalmology, Kanazawa University Graduate School of Medical Science, Kanazawa, Japan; 3Shimamoto Ophthalmology Clinic, Fukui, Japan; 4Department of Nutritional Sciences for Well-Being, Faculty of Health Sciences for Welfare, Kansai University of Welfare Sciences, Osaka, Japan; 5Department of Applied Biological Chemistry, Faculty of Agriculture, Kindai University, Nara, Japan; 6Inary Co., Ltd., Tokyo, JapanCorrespondence: Koji NittaDepartment of Ophthalmology, Fukui-ken Saiseikai Hospital, 7-1 Funabashi, Wadanaka-cho, Fukui 918-8503, JapanTel +81 776 23 1111Fax +81 776 28 8515Email nitta.koji7001@fukui.saiseikai.or.jpBackground: This retrospective study evaluated the effect of adjunctive administration of brimonidine 0.1% on disc hemorrhage (DH) in patients with primary open-angle glaucoma or normal-tension glaucoma who were already treated with other anti-glaucoma drugs.Methods: Patients with DH, before adjunctive therapy with brimonidine, were enrolled. Subjects were excluded if their treatment regimen was changed within 1 year after initiation of adjunctive therapy with brimonidine. We investigated the frequency of DH and intraocular pressure (IOP). Both parameters were compared before and after adjunctive administration of brimonidine.Results: The frequency of DH before and after brimonidine administration was 0.67± 0.68 and 0.31± 0.72 times/year, respectively, with a significant decrease (P=0.01), and the mean IOP before and after brimonidine administration was 12.5± 1.9 and 11.2± 2.2 mmHg, respectively, (P=0.0006) with a significant reduction after adjunctive administration.Conclusion: The results of this study supported the hypothesis that the frequency of DH is reduced by brimonidine alongside lowering of IOP.Keywords: disc hemorrhage, intraocular pressure, brimonidine, primary open-angle glaucoma, normal-tension glaucoma